Laser speckle correlation as a non-contact ocular microtremor measurement technique - Kenny, Emer (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2014)
Ocular microtremor (OMT) is high frequency, low amplitude fixational eye movement present in all healthy people. It occurs even while the eye appears to be at rest. Benefits of measuring OMT have been proven in a number of clinical conditions. For example, in coma the peak frequency of OMT is known to decline, while for brain stem death, no peak frequency is present.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin